Easy‐Curing and pH‐Regulated CRISPR‐Cas9 Plasmids for Gene Editing and Plasmid Curing in Lactococcus cremoris - Javier Nicolás Garay‐Novillo; José Ángel Ruiz‐Masó; Gloria delSolar; José Luis Barra (Microbial Biotechnology)
ABSTRACT In this work, we developed a plasmid‐based CRISPR‐Cas9 strategy for editing Lactococcus cremoris, which allows easy generation of plasmid‐free strains with the desired modification. We constructed versatile shuttle vectors based on the theta‐type pAMβ1 promiscuous replicon and p15A ori, expressing both the Cas9 nuclease gene (under pH‐regulated promoters derived from P170) and a single‐guide RNA for specific targeting (under a strong constitutive promoter). The vectors designed for plasmid targeting were very effective for low‐ and high‐copy‐number plasmid curing in L. cremoris, and their targeting efficiency was shown to be tunable by regulating cas9 expression. For chromosome editing, we implemented a host‐independent method that enhances double‐homologous recombination events using plasmids expressing the genes encoding λRed‐phage Redβ recombinase and Escherichia coli single‐stranded DNA binding protein (EcSSB). By coupling either the endogenous recombination machinery or the Redβ‐EcSSB‐assisted recombination system with our novel chromosome‐targeting CRISPR‐Cas9 plasmids, we efficiently generated and selected thousands of gene‐edited cells. Examination of the impact of the constructed CRISPR‐Cas9 vectors on host fitness revealed no Cas9‐associated toxicity, and, remarkably, these vectors exhibited a very high loss rate when growing the bacterial host cells in the absence of selective pressure.